The effect of syringin on the expression of TNF-α, iNOS, ICAM-1 and its' mRNA in the heart, brain and kidneys of spontaneously hypertensive rats - U.S. Mahadeva, Rao; Thant, Zin; Shanmuga, Sundaram (2016)
To investigate the effect of syringin (SYN) on TNF-α, iNOS, ICAM-1 and its’ mRNA expression in the heart, brain and kidneys of spontaneously hypertensive rats (SHR), and reveal the mechanism of its anti-inflammatory injury in hypertension target organs. SHRs were randomly divided into 5 groups including the model group (Group-2), the high-dose (G-4), medium-dose (G-5), low-dose (G-6) SYN group and the benazepril group (G-3), with 5 rats in each group. Wistar Kyoto (WKY) rats were used for the normal control group (G-1). Non-invasive blood pressure (BP) instruments were used to measure systolic blood pressure in the rats tail artery; used western blot to analyze the expression of TNF-α, iNOS, ICAM-1 and used reverse transcription-polymerase chain reaction (RT-PCR) to analyze the expression of TNF-α, iNOS, ICAM-1 mRNA. Compared with the normal control group, the model group’s BP level was significantly increased (P0.05); compared with the normal control group, the expression of TNF-α, iNOS, ICAM-1 and its’ mRNA in the model group was significantly increased (P0.05). SYN had no significant BP lowering effect; SHR showed inflammatory injury in the heart, brain and kidneys; improvement on the inflammatory injury, and in turn, the anti-inflammation mechanism may be associated with lowering TNF-α, iNOS and ICAM-1 and its’ mRNA expression.